2013
DOI: 10.1309/ajcpxv64gxlzciga
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Ability of a CK5/p63/CK8/18 Antibody Cocktail in Stratifying Breast Papillary Lesions on Needle Biopsy

Abstract: Although a single stain or combination cannot independently stratify papillary lesions, a CK5/p63/CK8/18 antibody cocktail is a useful adjunct to morphology for evaluating breast papillary lesions in needle biopsy specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…The present study has determined that myoepithelial markers (SMA & p63) associated with CK14 exhibit significantly higher expression rates in benign lesions in comparison to malignant lesions as evidenced by (P < .00), with high specificity (100%) and low sensitivity (63.3%). It is suggested that combined panel of P63, SMA, and CK14 may be utilized as reliable markers for distinguishing between benign and malignant papillary breast lesions.in agreement with previous work (29) which concluded that CK5/p63/CK8/18 antibody cocktail is a useful adjunct to morphology for evaluating breast papillary lesions. Chromogranin (CG) is of commonly used neuroendocrine markers, it was found to be negatively expressed in papilloma but highly positive in solid papillary carcinoma with more specificity 95% and less sensitivity 29% respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The present study has determined that myoepithelial markers (SMA & p63) associated with CK14 exhibit significantly higher expression rates in benign lesions in comparison to malignant lesions as evidenced by (P < .00), with high specificity (100%) and low sensitivity (63.3%). It is suggested that combined panel of P63, SMA, and CK14 may be utilized as reliable markers for distinguishing between benign and malignant papillary breast lesions.in agreement with previous work (29) which concluded that CK5/p63/CK8/18 antibody cocktail is a useful adjunct to morphology for evaluating breast papillary lesions. Chromogranin (CG) is of commonly used neuroendocrine markers, it was found to be negatively expressed in papilloma but highly positive in solid papillary carcinoma with more specificity 95% and less sensitivity 29% respectively.…”
Section: Discussionsupporting
confidence: 87%
“…P63 and Ki67 data presented in this study reinforced the statements of a large part of the authors, who affirm that the use of isolated markers is not sufficiently selective to separate benign from malignant and atypical lesions [10][11][12] .…”
Section: Discussionsupporting
confidence: 84%
“…Several markers can be used for breast tumors. In this work we used p63, a nuclear protein expressed in the basal epithelium of several organs, which in the breast has its positivity close to 100%, when the extracellular matrix is normal and in benign proliferative lesions; and Ki67, a protein whose function is associated with cell replication, staining nuclei at any stage of the cell cycle except G0 [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%